Postoperative bowel herniation in a 5-mm nonbladed trocar site - Huang, Marilyn; Musa, Fernanda; Castillo, Caroline; Holcomb, Kevin (Journal of the Society of Laparoendoscopic Surgeons, 2010)
Incisional hernias are a rare complication of laparoscopic surgery, with a reported incidence of <1%. We describe a case of bowel herniation and strangulation involving a 5-mm trocar site. Although there is growing literature supporting fascial closure of abdominal port sizes ≥ 10 mm, there is sparse data to suggest closure of 5-mm port sites. Our case illustrates that in appropriate clinical scenarios, the possibility of a strangulated hernia involving a 5-mm port site warrants consideration.